Atrial fibrillation and atrial flutter – the state of the art. Part 1 - Janion-Sadowska, Agnieszka; Turek, Łukasz; Dudek, Aneta; Andrychowski, Jarosław; Sadowski, Marcin (Medical Studies/Studia Medyczne, 2021)
Despite constantly updating our knowledge on atrial fibrillation and flutter, there are still many questions and doubts about the nature and extent of the arrhythmic and non-arrhythmic consequences of these arrhythmias. In part 1 of the state-of-the-art paper the diagnostic work-up of patients with the 2 arrhythmias has been summarized. The management of patients with atrial fibrillation and flutter requires a multidisciplinary approach in the risk assessment (including stroke) and treatment strategy. Regardless of the type of antiarrhythmic or anticoagulant therapy, benefits must always surpass or at least offset potential adverse effects and drug toxicity.